Strategi Bisnis E-Commerce Dalam Optimalisasi Tingkat Hunian Kamar Hotel Dan Villa - Ida Bagus Fajar Eka Putra; Ida Bagus Teddy Prianthara (Universitas Pendidikan Nasional, 2019)
ABSTRACTConventional market transformation into a digital market is influenced by the development of E-commerce technology. Conventional marketing previously used as a marketing media has diminished with the presence of E-commerce technology, conventional market considered to have a shortage in terms of high costs and narrow market reach. The presence of E-commerce is able to expand the market with internet media as a distribution of information to prospective customers. The results of this study found Avilla Group to deal with competitors. Avilla Group using offline and Online market mix techniques in the process of marketing rooms. The offline market is still maintained for maintenance purposes for some customers who have more trust in offline travel agents. The average occupancy rate of units consists of 40% offline and 60% online. E-commerce marketing on Avilla Group is supported by 2 main systems, which are internal system and the Channel manager. The results of SWOT analysts obtain system development innovation instruments to face competitors can be developed on internal systems, so that the strength and opportunities of the online market can be maximized which has an impact on optimal room occupancy rates.